Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1271/bbb.68.384
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of Raffinose Promotes Calcium Absorption in the Large Intestine of Rats

Abstract: We examined the effects of feeding raffinose on intestinal calcium absorption in ovariectomized rats by two separate experiments. In experiment 1, female Sprague-Dawley rats (6 wk old) were divided into two groups: sham operation and ovariectomy, and fed diets with or without raffinose (30 g/kg diet) for 4 wk. In experiment 2, ovariectomized rats with cecocolonectomy or transsection and reanastomosis (sham) were divided into two groups as in experiment 1 and fed the same diets for 3 wk. In experiment 1, calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…It is well known that parathyroid hormone and 1,25-dihydroxyvitamin D3 [1,25(OH) 2 D 3 ] are important hormones involved in regulating intestinal calcium absorption. 32) The parathyroid glands sense the serum calcium level, and secrete parathyroid hormone (PTH) if it becomes too low, for example, when dietary calcium intake is inadequate. PTH stimulates the activity of the 1-hydroxylase in the kidney, resulting in increased production of calcitriol, the biologically active form of vitamin D3.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that parathyroid hormone and 1,25-dihydroxyvitamin D3 [1,25(OH) 2 D 3 ] are important hormones involved in regulating intestinal calcium absorption. 32) The parathyroid glands sense the serum calcium level, and secrete parathyroid hormone (PTH) if it becomes too low, for example, when dietary calcium intake is inadequate. PTH stimulates the activity of the 1-hydroxylase in the kidney, resulting in increased production of calcitriol, the biologically active form of vitamin D3.…”
Section: Discussionmentioning
confidence: 99%
“…One of the few studies investigating the effects of honey on calcium metabolism reported a higher calcium retention in infants fed honey-supplemented milk than control (21). Various studies based on animal models have also observed the calcium uptake-enhancing effects of raffinose (1,4,5), which is present in honey (22). In the present study, we investigated the acute and chronic effects of honey and its carbohydrate constituents (specifically glucose, fructose, and raffinose) on calcium absorption in growing rats by applying an isotopic tracer method (based on femur uptake of 45 Ca).…”
Section: Introductionmentioning
confidence: 99%
“…Honey is a commonly used sweetener consisting of the carbohydrates of fructose, glucose, and raffinose. Various studies with animal models have documented the calcium uptake-enhancing effects of raffinose [ 32 , 33 ] which was also present in honey used for this study.…”
Section: Discussionmentioning
confidence: 99%